Formation of emotional intelligence of students in biochemistry classes by means of dialogical learning (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the necessary of formation of the would-be teachers’ emotional intelligence at a higher educational institution. Also some ways and methods of the solution of the problem of formation of emotional intelligence in the course of studying biochemistry are considered.
Keywords: emotional intelligence; gradual formation; emotional intelligence formation standards; dialogue training